Synthetic Approaches to Various Class of Topoisomerase II Inhibitors - Dev, Sanal; Gabhe, Nishad; Dhaneshwar, S.R.; Joy, Monu; Mathew, Bijo (Mini-Reviews in Organic Chemistry, 2017)
Considering the diverse applications and importance of DNA topoisomerases II (TOP II) inhibitors in biological systems, it is vital to understand the fundamental organic chemistry of these inhibitory agents through various synthetic strategies and it is crucial for further developments of the same. Many of the reported TOP II inhibitors are associated with extreme structural complexities and require multi-step synthetic routes providing difficulties towards their preparation and modifications. The present work describes the synthetic protocols for a diverse array of candidates relating to both TOP II poisons and catalytic inhibitors which may be useful for further synthetic developments.
Keywords: Topoisomerase II